A. Six years experience on plant identification services: a case study in Herbarium Bogoriense - Alex Sumadijaya (BRIN Publishing (Penerbit BRIN), 2012)
The Herbarium Bogoriense (BO), an integrated part of the Botanical Division, Research Center for Biology, Indonesian Institute of Sciences, receives plant specimens to be identified on a daily basis.Â In a six year period from 2005 to 2010, data were extracted from thousand of identification requests by hundreds of clients. Patterns were observed based on variables such as time, plant groups, client expertises, and taxonomic level.Â Outputs from these analysis are being expected to become one of the pillar to build a unifying scheme for botanical research at the Herbarium Bogoriense by focusing on human resources development to deal with biodiversity issues about frequently encountered taxa.